Acute extreme hypocapnia and diabetic coma in an elderly patient after surgery: A case report - Strecker, Thomas; Siegle, Michaela; Bremer, Frank Felix (SAGE Open Medical Case Reports, 2024)
Hyperglycemia and diabetic ketoacidosis are serious and life-threatening emergencies in diabetes patients. Early recognition of the symptoms of these disorders and their management are essential. Therapy is adequate rehydration, insulin treatment, electrolyte replacement, and handling of the underlying causative disease. Herein, we present an 83-year-old male with an extremely altered blood gas analysis after a surgical procedure of his left hand due to a phlegmon and describe the successful treatment through intensive care.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Diabetes; hyperglycemia; hypocapnia; respiratory medicine; surgery

Ethical conflicts associated with COVID-19 pandemic, triage and frailty-unexpected positive disease progression in a 90-year-old patient: A case report. - Wehrfritz, Andreas; Schmidt, Joachim; Bremer, Frank Felix; Lang, Anne-Katharina; Welzer, Jacob; Castellanos, Alvaro Ixchel (Clinical Case Reports, 2023)
During the COVID 19 pandemic, advanced age, scoring systems, and a shortage of ICU beds were used as cut-offs for ICU admission. This case report describes the epicrisis of an elderly patient who was almost mistakenly not treated in an ICU.
EVALuna2:547214

Is COVID-19-associated pulmonary aspergillosis (CAPA) a myth? Frequency of Aspergillus detection from respiratory samples in intensive care unit patients with and without COVID-19 - Kuemmig, T.; Esse, Jan; Herbst, Larissa; Castellanos, I.; Strauss, Richard; Geißdörfer, Walter; Mihai, Sidonia; Rakova, Natalia; Cipa, Franziska; Pflaum, D.; Werblow, M.; Lang, Anne-Katharina; et al. (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

β-(1→3)-D-glucan- and mannan-guided early termination of antifungal therapy in ICU patients: a randomized controlled study - Erb, Timothy; Mihai, Sidonia; Strauss, Richard; Herbst, Larissa; Castellanos, Ixchel; Diesch, Katharina; Cipa, Franziska; Bihlmaier, Karl; Lang, Anne-Katharina; Ganslmayer, Marion; Willam, Carsten; Bremer, Frank Felix; et al. (Antimicrobial Agents and Chemotherapy, 2023)
Candida spp. are frequently encountered in specimens from ICUs. However, most of these detections represent colonization. Nevertheless, clinical practice shows that a considerable proportion of these patients will receive antifungal therapy (AT). β-(1→3)-D-glucan (BDG) and mannan are fungal biomarkers with high negative predictive values. We aimed to examine whether biomarker-guided discontinuation of AT can reduce the antifungal consumption. Therefore, we conducted a prospective, randomized intervention study between 1 April 2019 and 31 March 2020. All adult ICU patients with a newly started systemic AT but without fungal infection were eligible for inclusion. Enrolled patients were randomized into an intervention and a control group. In both groups, serum BDG and mannan were determined on days 1 and 2 of AT. If all measurements were negative, AT was discontinued in the intervention group. The primary endpoint was antifungal use. The study was terminated after 12 months. Until this time-point, 41 patients had been included. In the intervention group (n = 19), AT was stopped in only two patients because all others showed either positive BDG and∕or mannan levels. One of these two patients developed candidemia and AT had to be restarted. There was no significant difference in the primary and secondary endpoints. In summary, the strategy of using two negative BDG and mannan levels to stop AT failed to reduce antifungal consumption in our cohort. Indeed, there will inevitably be patients with invasive candidiasis in whom necessary AT is discontinued. The optimal patient population, biomarker set, and termination criteria are critical to the success of biomarker-based termination strategies.
CRIS-Team Scopus Importer:2023-12-15
Keywords: antibiotic stewardship; antifungal therapy; biomarker; Candida infection; candidemia; candidosis; discontinuation; fungal infection